Allgrove or 4 "A" syndrome: an autosomal recessive syndrome causing multisystem neurological disease. Issue 5 (1st May 2003) - Kimber, J; McLean, B N; Prevett, M; Hammans, S R
Abstract : Allgrove's or "4 A" syndrome is a rare autosomal recessive condition with alacrima, achalasia, autonomic disturbance, and ACTH insensitivity among other features. Recent studies have identified mutations in the AAAS, a candidate gene on chromosome 12q13 in such patients. Manifestations in adult patients are rarely reported. The syndrome usually presents during the first decade of life with dysphagia or severe (occasionally fatal) hypoglycaemic or hypotensive attacks, related to adrenocortical insufficiency. Onset of adrenal insufficiency or other features may be delayed to adulthood. In contrast with paediatric patients, adult patients with Allgrove's syndrome may present with multisystem neurological disease; the childhood history of achalasia or alacrima may be overlooked. The authors describe two families with two affected siblings and a further unrelated patient with typical clinical features of Allgrove's syndrome, who exhibit signs of multisystem neurological disease including hyperreflexia, muscle wasting, dysarthria, ataxia, optic atrophy, and intellectual impairment. None of the cases have developed adrenal insufficiency but all have progressive neurological disability. Autonomic dysfunction was a significant cause of morbidity in two cases. The three index cases represent the longest described follow up of Allgrove's syndrome into adulthood. It is speculated that they represent a subgroup of patients who follow an often undiagnosed chronic neurological course. Recognition of the syndrome presenting in adult life permits treatment of unrecognised autonomic dysfunction, adrenal insufficiency and dysphagia, and appropriate genetic advice.